Later prehistoric monuments of Northern Portugal : some remarks - Jorge, Susana Oliveira (1998)
This text deals with prehistoric "monuments" in the strict sense, structures which are architecturally prominent in the landscape. We shall be discussing burial mounds, enclosures with stelae or those surrounded by walls or by stone platforms. We are clearly excluding all sites which, although monuments in a wider sense, do not correspond to the above characteristics (rock-art sites, open air settlements, non-monumental graves, dwelling – or storage – places in rock shelters, etc.). These "monuments" are looked at from the double perspective of their relationship with the landscape, and of their role as arenas of social dispute and consolidation of identity.